2011
DOI: 10.1109/tpami.2010.203
|View full text |Cite
|
Sign up to set email alerts
|

Facial Deblur Inference Using Subspace Analysis for Recognition of Blurred Faces

Abstract: This paper proposes a novel method for recognizing faces degraded by blur using deblurring of facial images. The main issue is how to infer a Point Spread Function (PSF) representing the process of blur on faces. Inferring a PSF from a single facial image is an ill-posed problem. Our method uses learned prior information derived from a training set of blurred faces to make the problem more tractable. We construct a feature space such that blurred faces degraded by the same PSF are similar to one another. We le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 29 publications
0
51
0
Order By: Relevance
“…Motion blur, however, occurs when exposure time is not brief enough due to the rapid object moving or camera shaking. There are two main categories of approaches for improving the quality of the blurred face images: 1) blurred image modelling using methods such as subspace analysis [55] or sparse representation [82], and 2) blur-tolerant descriptor based methods which attempt to extract blur insensitive features such as Local Phase Quantization (LPQ) [1], [25].…”
Section: Face Recognition Algorithmsmentioning
confidence: 99%
“…Motion blur, however, occurs when exposure time is not brief enough due to the rapid object moving or camera shaking. There are two main categories of approaches for improving the quality of the blurred face images: 1) blurred image modelling using methods such as subspace analysis [55] or sparse representation [82], and 2) blur-tolerant descriptor based methods which attempt to extract blur insensitive features such as Local Phase Quantization (LPQ) [1], [25].…”
Section: Face Recognition Algorithmsmentioning
confidence: 99%
“…Work in the recognition of blurred faces [33] is also related to our method. Their approach extracts features from motion-blurred images of faces and then uses the subspace distance to identify the blur.…”
Section: Blurred Face Recognitionmentioning
confidence: 99%
“…The performances of face recognition could suffer from blur for the fact that blur leads to two main problems [6]:…”
Section: Introductionmentioning
confidence: 99%
“…A PSF is inferred through total variation regularization [16], the variation of Gaussian scale in the edges [17][18] [19], or variation in the wavelet domain [20] [21]. Recently, M. Nishiyama [6] has revealed that deblurring from a single image is an ill-posed problem and these deblurring methods are insufficient for accurate face recognition. Other methods deduce a PSF using multiple images [22][23], and M. Nishiyama et.al [6] [24] propose to build multiple PSFs and use the best match as the final PSF.…”
Section: Introductionmentioning
confidence: 99%